HTT loss-of-function contributes to RNA deregulation in developing Huntington’s disease neurons - Emilia Kozłowska; Agata Ciołak; Grażyna Adamek; Julia Szcześniak; Agnieszka Fiszer (Cell & Bioscience)
Abstract Background Huntington’s disease (HD) is a neurodegenerative disorder caused by the expansion of CAG repeats in the HTT gene, which results in a long polyglutamine tract in the huntingtin protein (HTT). One of the earliest key molecular mechanisms underlying HD pathogenesis is transcriptional dysregulation, which is already present in the developing brain. In this study, we searched for networks of deregulated RNAs crucial for initial transcriptional changes in HD- and HTT-deficient neuronal cells. Results RNA-seq (including small RNAs) was used to analyze a set of isogenic human neural stem cells. The results were validated using additional methods, rescue experiments, and in the medium spiny neuron-like cells. We observed numerous changes in gene expression and substantial dysregulation of miRNA expression in HD and HTT-knockout (HTT-KO) cell lines. The overlapping set of genes upregulated in both HD and HTT-KO cells was enriched in genes associated with DNA binding and the regulation of transcription. We observed substantial upregulation of the following transcription factors: TWIST1, SIX1, TBX1, TBX15, MSX2, MEOX2 and FOXD1. Moreover, we identified miRNAs that were consistently deregulated in HD and HTT-KO cells, including miR-214, miR-199, and miR-9. These miRNAs may function in the network that regulates TWIST1 and HTT expression via a regulatory feed-forward loop in HD. Conclusions On the basis of overlapping changes in the mRNA and miRNA profiles of HD and HTT-KO cell lines, we propose that transcriptional deregulation in HD at early neuronal stages is largely caused by a deficiency of properly functioning HTT rather than a typical gain-of-function mechanism.